Effects of tidal re-introduction design on sedimentation rates in previously embanked tidal marshes. (5th October 2020) - Oosterlee, Lotte; Cox, Tom J.S.; Temmerman, S.; Meire, P.
Abstract: Due to an increasing appreciation of the highly valuable ecosystem services of tidal marshes, an increasing number of projects are being implemented to re-introduce tides on formerly embanked land using a variety of 'soft' engineering techniques. However, the ecological development of the recreated tidal marshes largely depends on the design of the project, as this determines the hydro-geomorphological evolution. In this study we compare the hydro-geomorphological development in two marsh restoration projects in the Scheldt estuary (Belgium), one with a controlled reduced tidal exchange (CRT) and one with a full tidal exchange (FTE) between the marsh and adjacent estuary, based on ten years (CRT) and five years (FTE) of data on sedimentation/erosion rates, sediment properties and tidal characteristics. The results clearly show that the CRT technique strongly reduces the input of sediments, whereas larger water depths in the FTE led to extremely high sedimentation rates of 60–400 cm yr −1 in the first 2.5 months. The rapidly accreting sediments in the FTE consolidated much less than in the CRT and this poor sediment consolidation may have contributed to slower vegetation and benthos colonization in the FTE. This comparison of two different tidal systems can serve as an example to show the effect of different techniques to re-introduce tides on the creation of tidal marshes on low-lying areas. Depending on the tidal marsh development goals, different hydrologic regimes and thereby different sedimentation rates may be desired. For example, when the objective is to contribute to estuarine flood risk mitigation by creating and maintaining a high water buffering capacity in restored tidal marshes, a CRT system with low sedimentation rates is preferred. However, when the objective is to build up soil elevation, for example as an adaptation to sea level rise, the FTE technique as studied here could be a good way to trap sediments. Graphical abstract: Image 1 Highlights: Tidal re-introduction using controlled reduced tide strongly reduces input of sediments. Full tidal exchange in low-lying areas results in high sedimentation rates. Controlled reduced tide is defined by extended flooding and reduced tidal amplitude. Full tidal exchange results in exact copy of natural tide in restoration area.